Polishing pad material and preparation method and application thereof

By controlling the moisture content of the impregnated cloth and the concentration of N,N-dimethylformamide solution, a stable and uniform microporous structure is formed, which solves the problem of many surface defects of the silicon wafer after grinding of the existing soft polishing pad materials, and improves the polishing effect.

CN119871213APending Publication Date: 2025-04-25QUZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510118294.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

After the existing soft polishing pad materials are ground, there are many defects on the surface of the silicon wafer, which is difficult to meet the requirements of semiconductor integrated circuit manufacturing.

Method used

By controlling the moisture content of the impregnated cloth and the concentration of the N,N-dimethylformamide solution during solidification and forming, the orderly arrangement of the polyurethane chains is promoted to form a stable and uniform microporous structure.

Benefits of technology

The surface defects of the polished wafer wafer are reduced, the performance of the polishing pad material is improved, and it can be successfully applied to chemical mechanical polishing processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871213A_ABST
    Figure CN119871213A_ABST
Patent Text Reader

Abstract

The invention relates to the field of chemical mechanical polishing, in particular to a polishing pad material and a preparation method and application thereof. The method is mainly characterized in that an N, N-dimethylformamide solution with a proper concentration is utilized to promote ordered arrangement of polyurethane chains during solidification and forming, and the proper water content of the impregnated cloth can ensure uniform solidification and forming of polyurethane. By controlling the water content of the impregnated cloth and the concentration of the N, N-dimethylformamide solution during solidification forming, the polishing pad material can form a stable and uniform microporous structure, so that the surface defects of a wafer silicon wafer polished by the soft polishing pad material are reduced, and the quality of the wafer silicon wafer is improved. The technical problem that many defects exist on the surface of a silicon wafer after an existing polishing pad material is ground is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical mechanical polishing, and in particular to a polishing pad material and a preparation method and application thereof. Background Art

[0002] Chemical mechanical polishing technology, with its unique material removal capability and surface treatment accuracy, not only occupies a core position in semiconductor integrated circuit manufacturing, but also demonstrates broad application potential and value in technical fields such as advanced material processing.

[0003] Polishing heads, polishing pads and polishing liquids are the core elements required for chemical mechanical polishing technology, which will have a significant impact on chemical mechanical polishing technology. With the continuous reduction in the size of semiconductor devices and the increase in structural complexity, the requirements for surface defects of polished silicon wafers used in semiconductor devices are getting higher and higher. Especially in the manufacture of integrated circuits at advanced nodes, even tiny surface defects may cause chip performance degradation or even failure.

[0004] Polishing pads can be divided into two categories according to hardness: hard pads and soft pads. Hard polishing pads are generally made of porous alumina or silicon nitride, while soft polishing pads are generally made of elastic materials such as polyurethane and polyetheretherketone. Among them, silicon wafers polished with existing soft polishing pad materials have many surface defects, which makes it difficult to meet the requirements of semiconductor integrated circuit manufacturing. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art, provide a polishing pad material and a preparation method and application thereof, and solve the technical problem that the existing polishing pad material has many surface defects on silicon wafers after grinding.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a polishing pad material, comprising the following steps: The impregnated cloth is immersed in water so that the moisture content of the impregnated cloth is between 25wt% and 28wt% to obtain a base; the polyurethane slurry is evenly coated on the surface of the base, and after solidification and forming in an N,N-dimethylformamide solution, an intermediate is obtained; the intermediate is washed, dried, and surface treated to obtain a polishing pad material; wherein the concentration of the N,N-dimethylformamide solution is 12wt% to 17wt%.

[0007] The present invention mainly utilizes N,N-dimethylformamide solution of appropriate concentration to promote the orderly arrangement of polyurethane chains during solidification and molding, and the appropriate water content of the impregnated cloth can ensure the uniform solidification and molding of polyurethane. The present invention controls the water content of the impregnated cloth and the concentration of the N,N-dimethylformamide solution during solidification and molding, so that the polishing pad material can form a relatively stable and uniform microporous structure, so as to reduce the surface defects of the wafer silicon slice after polishing by the soft polishing pad material, and solves the technical problem that the existing polishing pad material has many surface defects of the silicon slice after grinding.

[0008] Optionally, the coating thickness of the polyurethane slurry is 1.5 mm to 2.0 mm.

[0009] Optionally, the solidification forming comprises the following steps: The base coated with polyurethane slurry is immersed in N,N-dimethylformamide solution at a certain angle until it is completely immersed; the angle formed between the plane where the base coated with polyurethane slurry is located and the liquid surface of the N,N-dimethylformamide solution is α, and the size of α is 25° to 35°. When the size of α exceeds the range of 25° to 35°, the solidification and molding effect of the polyurethane slurry will be affected, and even bubble cavities will be formed in the solidified polyurethane coating.

[0010] Preferably, when the angle α is 30°, the coagulation and molding effect of the polyurethane slurry is best.

[0011] Optionally, the water washing treatment includes: intermittent water washing for 15 times, soaking in water for 5 minutes to 15 minutes, and then intermittent water washing for another 15 times.

[0012] Optionally, the surface treatment includes performing a grinding treatment and a grooving treatment in sequence, wherein the grinding treatment is used to expose the pore structure of the polishing pad material, and the grooving treatment is used to form a surface groove structure on the surface of the polishing pad material.

[0013] The invention provides a polishing pad material, which is prepared by the above-mentioned preparation method.

[0014] The present invention provides an application of the above-mentioned polishing pad material in chemical mechanical polishing processing.

[0015] Compared with the prior art, the beneficial effect of the present invention is that the present invention mainly utilizes an N,N-dimethylformamide solution of appropriate concentration to promote the orderly arrangement of polyurethane chains during solidification, and the appropriate water content of the impregnated cloth can ensure the uniform solidification of polyurethane. The present invention controls the water content of the impregnated cloth and the concentration of the N,N-dimethylformamide solution during solidification, so that the polishing pad material can form a relatively stable and uniform microporous structure to reduce the surface defects of the wafer silicon wafer after polishing by the soft polishing pad material, and solves the technical problem that the existing polishing pad material has many surface defects on the silicon wafer after grinding. Subsequent experimental results show that the polishing pad material prepared by the preparation method of the polishing pad material provided by the present invention can be successfully applied to chemical mechanical polishing processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials using different water contents provided by the present invention. Among them, Figures a) to e) are scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials prepared in Comparative Example 1, Example 1, Example 2, Comparative Example 2 and Comparative Example 3, respectively.

[0017] Figure 2 The present invention provides scanning electron microscope images of the cross-sectional microporous structure of the polishing pad material solidified by N,N-dimethylformamide solution of different concentrations. Among them, Figures a) to d) are scanning electron microscope images of the cross-sectional microporous structure of the polishing pad material prepared in Comparative Examples 4 to 7, Figures e) to g) are scanning electron microscope images of the cross-sectional microporous structure of the polishing pad material prepared in Example 1, Example 3 and Example 4, and Figures h) to k) are scanning electron microscope images of the cross-sectional microporous structure of the polishing pad material prepared in Comparative Examples 8 to 11.

[0018] Figure 3 The scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials provided by the present invention using polyurethane slurry with different coating thicknesses are shown in Figures a) to c) respectively.

[0019] Figure 4 This is a diagram illustrating the distribution of sampling points for the surface pore size analysis test of the polishing pad material provided by the present invention.

[0020] Figure 5 This is a statistical diagram of the pore sizes at sampling points of the polishing pad material A provided by the present invention.

[0021] Figure 6 This is a statistical diagram of the pore sizes at sampling points of the polishing pad material B provided by the present invention.

[0022] Figure 7The scanning electron microscope images of the cross-sections of different polishing pad materials provided by the present invention are shown in FIG. a) shows the micropore structure of polishing pad material A', FIG. b) shows the micropore structure of polishing pad material A, and FIG. c) shows the micropore structure of polishing pad material B.

[0023] Figure 8 The present invention provides scanning electron microscope images of the surfaces of different polishing pad materials and corresponding Image J software analysis images. In the figure, a) is a scanning electron microscope image of the surface of polishing pad material A, b) is an Image J software analysis image corresponding to a), c) is a scanning electron microscope image of the surface of polishing pad material B, and d) is an Image J software analysis image corresponding to c).

[0024] Fig. 9 This is a statistical comparison chart of the number of holes per unit area of ​​different polishing pad materials provided by the present invention.

[0025] Fig.10 This is a statistical comparison chart of the pore areas of different polishing pad materials provided by the present invention.

[0026] Fig.11 This is a statistical comparison chart of the porosity of different polishing pad materials provided by the present invention.

[0027] Fig.12 This is a comparative diagram of the correlation between the unevenness and oxide removal rate of different polishing pad materials provided by the present invention.

[0028] Fig.13 The defect distribution comparison diagram of different polishing pad materials provided by the present invention. Among them, Figures a) to c) are defect diagrams corresponding to test condition 1 in Table 4; Figures d) to f) are defect diagrams corresponding to test condition 2 in Table 4; Figures g) to i) are defect diagrams corresponding to test condition 3 in Table 4. DETAILED DESCRIPTION

[0029] In order to solve the above technical problems, the present invention provides a polishing pad material and a preparation method and application thereof. The technical scheme and embodiments of the present invention are now described in detail in conjunction with the accompanying drawings.

[0030] The present invention provides a method for preparing a polishing pad material, comprising the following steps: Preparation of coating slurry: Prepare the test coating slurry with a 1000ml measuring cylinder according to the test content requirements. First, add a certain amount of N,N-dimethylformamide to the measuring barrel and mix it with pure water, and then add a certain amount of polyurethane resin and color paste. Use a mixer to stir at a speed of 500r / min for 20 minutes. At the same time, adjust the rotor length during the stirring process so that the rotor moves up and down to stir evenly. After stirring, place the coating slurry in a vacuum machine for vacuuming. After the bubbles disappear completely, take out the slurry to be coated and seal the mouth of the measuring cylinder with plastic wrap.

[0031] Control the moisture content: Use a knife to cut a 15cm×15cm impregnated cloth, soak it in a pre-solidification tank for 10 minutes, then take it out, adjust the moisture content by the gap between the rolling mills, and use a moisture content detector to measure the moisture content of the front, middle and back sections to get the average value. The treated impregnated cloth is called Bess.

[0032] Coating: Take out a glass plate and wipe it with a non-woven cloth soaked in alcohol. Fix the bass with measured water content on the glass plate with tape. At this time, you need to fix the top of the bass first, then fix the left side, flatten the bass by hand, then fix the right side, and finally fix the bottom. When fixing, stick the tape to the edge of the bass. In order to leave more area for coating. Place the pasted glass plate on the large glass plate, fix the two glass plates together with tape, and place 2mm pads on both sides of the bass. Pour 40ml of slurry horizontally, use a clean steel stick to slide at a uniform speed and parallel, use a scraper to clean the slurry around, and stay for 30s before entering the water.

[0033] Solidification: Use a knife to remove the ruler, and place the base coated with polyurethane slurry into a solidification tank filled with N,N-dimethylformamide solution. Do not hit the side of the tank. The solidification time is 30 minutes. Insert mercury into the solidification tank to measure the solidification temperature.

[0034] The angle between the plane of the base coated with the polyurethane slurry and the liquid surface of the N,N-dimethylformamide solution is 30°. When the angle is 30°, the coagulation and molding effect of the polyurethane slurry is the best.

[0035] Washing: Take out the sample and wash it 15 times with water in the padding interval to avoid the orange peel phenomenon. Soak it in pure water for 10 minutes and then wash it 15 times with water again using the padding machine.

[0036] Drying: Place the sample on a pad, fix it with clips to prevent warping, and dry it in a vacuum oven at 90°C for 30 minutes before taking it out.

[0037] Surface processing: The dense layer of the polyurethane film is ground away by a grinding wheel roller to expose the top of the finger-shaped holes.

[0038] Grooving: The heated embossing roller is used to heat press the patterns on the film surface to form patterns. Grooving can improve the uniformity of the polishing pressure distribution of the polishing pad material, which is beneficial to improving the processing quality.

[0039] The information of the manufacturers and specifications of the main raw materials used in the present invention is shown in Table 1: Table 1 Production raw material information The present invention is described in detail below through specific examples. The examples are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0040] Example 1 This embodiment provides a method for preparing a polishing pad material, which specifically includes the following steps: Step 1, preparation of polyurethane slurry.

[0041] According to the test requirements, use a 1000ml measuring cylinder to prepare the test coating slurry. First, add 127g of N,N-dimethylformamide into the measuring barrel and mix it with 22g of pure water, then add 438g of polyurethane resin, 22g of color powder and dispersant to form a color paste, where the mass proportion of the dispersant in the polyurethane slurry is 0.5%. Use a mixer to stir at a speed of 500r / min for 20 minutes, and adjust the rotor length during the stirring process so that the rotor moves up and down to stir evenly. After stirring, use a vacuum machine to vacuum the polyurethane slurry until the bubbles disappear completely, then take out the polyurethane slurry and seal the mouth of the measuring cylinder with plastic wrap.

[0042] Step 2, preparation of bass.

[0043] The impregnated cloth with a size of 15 cm×15 cm was immersed in a pre-coagulation tank filled with water, and was taken out after immersion for 10 minutes. The water content was adjusted by the gap between the rolling mills so that the water content of the impregnated cloth was 25wt%, and the bass was obtained.

[0044] Step 3, preparation of intermediates.

[0045] Take out a glass plate and wipe it with a non-woven cloth soaked in alcohol. Fix the base on the glass plate with tape. When fixing, stick the tape to the edge of the impregnated cloth to leave more area for coating. Place the pasted glass plate on the large glass plate, fix the two glass plates together with tape, and place 2mm pads on both sides of the impregnated cloth. Pour 40mL of polyurethane slurry horizontally, use a clean steel stick to slide at a uniform speed and parallel, use a scraper to clean the slurry around, and stay for 30 seconds before applying in water.

[0046] The ruler is removed with a knife, and the bess coated with the polyurethane slurry is placed in a coagulation tank filled with N,N-dimethylformamide solution to perform coagulation molding operation to obtain an intermediate.

[0047] The solidification time is 30 minutes, and the concentration of the N,N-dimethylformamide solution is 12%. When the base coated with the polyurethane slurry enters the N,N-dimethylformamide solution, an angle of 30° is formed between the plane of the base coated with the polyurethane slurry and the liquid surface of the N,N-dimethylformamide solution, and the coating thickness of the polyurethane slurry on the base is 1.5 mm.

[0048] Step 4: Preparation of polishing pad material.

[0049] The intermediate is washed, dried and surface treated to obtain a polishing pad material.

[0050] The washing step includes: washing the intermediate 15 times with a roller, soaking it in pure water for 10 minutes, and then washing it 15 times with a roller again to avoid the occurrence of orange peel. The drying step includes: placing the washed intermediate in a vacuum oven at a temperature of 90°C for 30 minutes. The surface treatment includes grinding and grooving. Grinding is to grind off the dense layer of polyurethane on the surface of the polishing pad material by a grinding wheel roller to expose the pore structure; grooving is to heat-press the texture on the surface of the polishing pad material after grinding by a heated embossing roller to form a surface groove structure.

[0051] Example 2 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the moisture content of the impregnated cloth in step 2 is 27 wt %.

[0052] Example 3 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 15%.

[0053] Example 4 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 17%.

[0054] Example 5 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: Refer to the preparation method of Example 1, except that the coating thickness of the polyurethane slurry on the bass in step 3 is 2 mm.

[0055] Example 6 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: Refer to the preparation method of Example 1, except that the moisture content of the impregnated cloth in step 2 is 28wt%, the concentration of the N,N-dimethylformamide solution in step 3 is 17%, and the coating thickness of the polyurethane slurry on the bass in step 3 is 1.5mm.

[0056] Comparative Example 1 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the moisture content of the impregnated cloth in step 2 is 22 wt %.

[0057] Comparative Example 2 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the moisture content of the impregnated cloth in step 2 is 30 wt %.

[0058] Comparative Example 3 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the moisture content of the impregnated cloth in step 2 is 35 wt %.

[0059] Comparative Example 4 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 0%, that is, water is used instead of the N,N-dimethylformamide solution.

[0060] Comparative Example 5 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 3%.

[0061] Comparative Example 6 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 5%.

[0062] Comparative Example 7 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 8%.

[0063] Comparative Example 8 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: Refer to the preparation method of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 20%.

[0064] Comparative Example 9 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 23%.

[0065] Comparative Example 10 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: Refer to the preparation method of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 25%.

[0066] Comparative Example 11 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: The preparation method is similar to that of Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 30%.

[0067] Comparative Example 12 This embodiment provides a method for preparing a polishing pad material, and the specific steps are as follows: Refer to the preparation method of Example 1, except that the coating thickness of the polyurethane slurry on the bass in step 3 is 2.5 mm.

[0068] Test 1: Scanning electron microscope test The shape and size of the micropores of the polishing pad material were studied using a scanning electron microscope. The polishing pad materials of Examples 1 to 5 and Comparative Examples 1 to 12 were vertically cut into surface and cross-sectional samples of 10 mm×10 mm×5 mm in size. The acceleration voltage of the scanning electron microscope was set to 15 kV.

[0069] The micropore shape of the polishing pad material is preferably a structure that obtains relatively regular "water drop-shaped" or "finger-shaped" holes. The finger-shaped structure is an excellent structure that is conducive to the polishing pad storing polishing liquid and obtaining a better polishing effect.

[0070] The results of the SEM test are as follows: The scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 are as follows: Figure 1 As shown, Figures a) to e) correspond to the scanning electron microscope images of the cross-sectional micropore structures of the polishing pad materials prepared in Comparative Example 1, Example 1, Example 2, Comparative Example 2 and Comparative Example 3, respectively. From the comparison of the micropore shapes in Figures a) to e), it can be seen that the micropore shapes of the polishing pad materials prepared in Examples 1 to 2 are closer to "water drop shapes" than those in Comparative Examples 1 to 3.

[0071] When the water content of the impregnated cloth is relatively small, less than 25%, a state of equilibrium will be formed between water and N,N-dimethylformamide, which limits the diffusion rate of the polyurethane resin solution. Water molecules gradually replace the N,N-dimethylformamide solvent in the slurry, but because the water content in the impregnated cloth is not too much, the microphase separation is relatively uniform and the micropores formed are relatively small. However, when the water content of the impregnated cloth exceeds 28%, the number of water molecules increases and the effect of water becomes more significant. This will cause the water molecules to form larger and more irregular gaps in the polyurethane resin when it diffuses, causing the micropore shape to become coarse. In summary, the preferred range of the water content of the impregnated cloth is 25wt% to 28wt%.

[0072] The scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials prepared in Example 1, Example 3, Example 4 and Comparative Examples 4 to 11 are as follows: Figure 2 As shown. Among them, a) to d) correspond to the scanning electron microscope images of the cross-sectional micropore structure of the polishing pad materials prepared in Comparative Examples 4 to 7, e) to g) correspond to the scanning electron microscope images of the cross-sectional micropore structure of the polishing pad materials prepared in Example 1, Example 3 and Example 4, and h) to k) correspond to the scanning electron microscope images of the cross-sectional micropore structure of the polishing pad materials prepared in Comparative Examples 8 to 11. From the comparison of the micropore shapes in a) to k), it can be seen that the micropore shapes of the polishing pad materials prepared in Example 1, Example 3 and Example 4 are closer to "water drop shape" than those in Comparative Examples 4 to 11.

[0073] At N,N-dimethylformamide concentrations below 12%, the faster the bidirectional diffusion rate of N,N-dimethylformamide and water, the easier it is to form a surface film, resulting in coarse micropores. As the concentration of N,N-dimethylformamide increases to 15%, interfacial pores gradually begin to appear between the polyurethane layer and the base of the wet coating film. This is because as the concentration of N,N-dimethylformamide increases, a large stress is generated on the interface, and polyurethane nucleates and precipitates when approaching the interface. When the concentration of N,N-dimethylformamide reaches 17%, the concentration gradient of each substance decreases rapidly, which improves the stability of polyurethane in the inner layer mixture and forms a uniform and delicate microporous structure. The area between the polyurethane layer and the base is called a dense layer. However, when the concentration of N,N-dimethylformamide increases to a certain extent, the higher the concentration of N,N-dimethylformamide, the thicker the dense layer, which hinders diffusion and cannot effectively form a uniform and delicate microporous structure, resulting in irregular microporous morphology and even the appearance of double-sided interfacial pores. In summary, the preferred range of N,N-dimethylformamide is 12 wt % to 17 wt %.

[0074] The scanning electron microscope images of the cross-sectional microporous structures of the polishing pad materials prepared in Example 1, Example 5 and Comparative Example 12 are as follows: Figure 3As shown, a) to c) correspond to the scanning electron microscope images of the cross-sectional micropore structures of the polishing pad materials prepared in Example 1, Example 5 and Comparative Example 12, respectively. From the comparison of the micropore shapes in a) to c), it can be seen that, relative to Comparative Example 12, the micropore shapes of the polishing pad materials prepared in Example 1 and Example 5 are closer to "water drop shape".

[0075] From the scanning electron microscope image, we can see that there are large differences between the microporous structures, which is caused by different solidification times. When the coating thickness is 1.5mm, the solidification time is faster, the mutual diffusion and phase separation of N,N-dimethylformamide and water are more uniform, and the formed microporous structure is close to the shape of a water drop. On the contrary, when the coating thickness is thicker, 2.5mm, the solidification time slows down, resulting in uneven mutual diffusion and phase separation of solvent and water, making the microporous structure obviously coarse and short.

[0076] The present invention uses the following tests to characterize the performance of polishing pad materials A, A' and B: A' is the type of polyurethane polishing pad prepared before the research of this project, and the preparation parameters are: N,N-dimethylformamide concentration of coagulation tank is 15%, water content of Bess is 25%, and coating thickness is 1.5mm. A is the preferred polyurethane polishing pad after the research, and the preparation parameters are: N,N-dimethylformamide concentration of coagulation tank is 17%, water content of Bess is 28%, and coating thickness is 1.5mm. The specific preparation steps are detailed in Example 6. B is the polishing pad material provided by Dow Chemical.

[0077] Hardness test: The test was conducted using a Shaw A-type measuring instrument in accordance with GB / T 2411-2008. The measuring points were distributed between the outermost circles of the polishing pad, with an average of 8 points. The test result was the average value of the 8 measuring points, and the result was calculated to an accuracy of 0.1 ShA.

[0078] Compression rebound rate test: Use a digital thickness gauge to measure according to JISK 6505-1995 artificial leather test regulations. The measuring points are distributed on the three points of the equilateral triangle of the polishing pad. Place the product under a fixed digital thickness gauge to measure the initial thickness, read the reading, and the thickness is m0. Place a pressure block and a pressure block bracket with a total weight of 250g, wait for 5 minutes and read the reading, at this time the thickness is m1. Remove the pressure block for 5 minutes to allow the product to recover its elasticity, put the measuring rod down again after 5 minutes, wait for 30 minutes and read the reading, at this time the thickness is m2.

[0079] The compression rate and rebound rate are calculated according to the following formulas: X1=(m0-m1) / m0×100%; X2=(m2-m1) / (m0-m1)×100%; In the formula: X1—compression rate of polishing pad, %; X2—rebound rate of polishing pad, %; m0—initial thickness of polishing pad, mm; m1—thickness of polishing pad after adding fixed pressure block, mm; m2—thickness of polishing pad after rebound, mm.

[0080] The test results are taken as the average value of 3 measurement points, and the results are calculated with an accuracy of 0.1%.

[0081] Surface opening size analysis test: The surfaces of polishing pad material A and polishing pad material B are evenly sampled and distributed, and 4 sampling points are determined, such as Figure 4 As shown, Figure 4 The numbers 1 to 4 in the figure represent the positions of the four sampling points. The distribution of the opening sizes of each sampling potential was observed and counted by scanning electron microscopy.

[0082] Porosity and porosity testing: ImageJ software was used to test the porosity and porosity of the SEM surface image, and the measurement method was the circumscribed ellipse Major and Minor; the circumscribed rectangle Width and Height.

[0083] Polishing test: The grinding rate test conducted by the polishing machine tester can evaluate the processing efficiency of the polishing pad on the surface oxide of the silicon wafer, the flatness of the polishing pad after processing, and even reflect the performance of the polishing pad, such as wear resistance, abrasive liquid absorption capacity, etc. Detailed test parameters are shown in Table 2 below.

[0084] Table 2 Chemical mechanical polishing rate test parameters Defect rate test: The defect rate of silicon wafer surface during chemical mechanical polishing is tested with a chemical mechanical polishing defect tester to evaluate the quality and efficiency of the polishing process. Defect rate testing is of great significance for optimizing the polishing process, improving the surface quality of silicon wafers, and reducing defect rates. The lower the defect rate, the stronger the ability of the applied polishing pad to remove defects on the silicon wafer surface, and the better the quality of the polishing pad. The defect rate test parameters and plan are shown in Tables 3 and 4 below.

[0085] Table 3 Chemical mechanical polishing defect test parameters Table 4 Test plan Test results: Table 5 Thickness of each layer of polishing pad Table 6 Physical properties of polishing pad materials A and B Figure 7 In the figure, a) is a microporous structure diagram of the polishing pad material A', b) is a microporous structure diagram of the polishing pad material A, and c) is a microporous structure diagram of the polishing pad material B. Figure 7 As shown in Table 5 and Table 6, the micropore structure of polishing pad material A' is coarse and distorted before process improvement, while the micropore structure of polishing pad material A after process improvement has been significantly optimized. Therefore, only micropore morphology comparison is performed, and physical property analysis of polishing pad material A' is not performed.

[0086] Hardness is the ability of the polishing pad to resist external forces, which directly affects the polishing effect of chemical mechanical polishing. A polishing pad with higher hardness has higher wear resistance and thermal stability, and can provide higher polishing efficiency and longer service life; a polishing pad with lower hardness has good elasticity and will cause fewer surface defects to the object being polished.

[0087] Depend on Figure 7 The thickness of each layer of the polishing pad is obtained by measuring and marking the microporous structure as shown in Table 5. The physical properties of the polishing pad are then analyzed as shown in Table 6. The summary and analysis are as follows: The hardness range of polishing pad material A is 87HA~91HA, and the hardness range of polishing pad material B is 88HA~94HA; the hardness of polishing pad material A and polishing pad material B are relatively close, indicating that polishing pad material A can replace imported polishing pad material B for polishing tasks with higher surface requirements; The groove design is consistent with imported polishing pads, with no major differences.

[0088] In terms of compression rate and rebound rate, the compression rate of polishing pad material A is slightly lower than that of polishing pad material B; while the rebound rate of polishing pad material A is slightly higher than that of polishing pad material B. This is related to the fact that the polyurethane layer of polishing pad material A is thicker than that of polishing pad material B. Under the same pressure, the compression rate is relatively low and the rebound rate is relatively high. Generally speaking, polishing pads with low compression rate and high rebound rate can recover their shape faster when the pressure is released, resulting in better finish. This was also confirmed in the subsequent polishing analysis for reducing defects during chemical mechanical polishing.

[0089] In summary, compared with the polishing pad material A' before the process improvement, the micropores of the polishing pad material A after the process improvement obviously reach the ideal water droplet structure, and the thickness of the polyurethane layer is increased, and it has better performance than the imported polishing pad material B.

[0090] Opening size analysis: like Figure 5As shown, the pore sizes at the four sampling points of polishing pad material A are concentrated in the range of 31 μm to 40 μm, accounting for 40%, 39%, 41% and 41% respectively. It can be seen that the pore sizes are relatively uniform.

[0091] like Figure 6 As shown in the figure, the pore sizes at sampling points 1 and 4 of polishing pad material B are mainly concentrated in the range of 31μm to 40μm, accounting for 40% and 37% respectively; the pore sizes at sampling points 2 and 3 are mainly concentrated in the range of 21μm to 30μm, accounting for 42% and 46% respectively. This shows that the pore size of polishing pad material B tends to expand or shrink in one direction, and the pore size distribution uniformity is poor. Combined with Figure 5 and Figure 6 From the overall statistical curve in , it can be seen that the overlap of the pore size curve of polishing pad material B is worse than that of polishing pad material A.

[0092] In summary, the surface openings of polishing pad material A are superior in terms of opening size uniformity compared to polishing pad material B. This will facilitate the flow and storage of the polishing liquid during the chemical mechanical polishing process and improve the flatness of the chemical mechanical polishing process.

[0093] Porosity and porosity analysis: Figure 8 Figure a) is a scanning electron microscope image of the surface of polishing pad material A, figure b) is an Image J software analysis image corresponding to figure a), figure c) is a scanning electron microscope image of the surface of polishing pad material B, and figure d) is an Image J software analysis image corresponding to figure c).

[0094] Depend on Figure 8 to Figure 11 As is known, the porosity of polishing pad material B is greater than that of polishing pad material A. Polishing pad material B has a higher porosity and more microscopic pore structures, which can better absorb and release polishing liquid during the polishing process, help reduce surface friction and heat accumulation, and is suitable for objects that require a longer polishing time. Polishing pad material A has a relatively lower porosity and relatively fewer microscopic pore structures.

[0095] Chemical Mechanical Polishing Rate Study: Relevance Fig.12 In the figure, the Nu value of polishing pad material A is significantly lower than those of polishing pad material A' and polishing pad material B, and the lower the Nu value, the smoother the surface. This is related to the physical properties of low compression rate and high rebound rate of polishing pad material A, as well as the more uniform pore size after optimizing the microporous structure through process improvement, which improves the Nu value and achieves the purpose of flattening.

[0096] Chemical Mechanical Polishing Defect Rate Analysis: Through chemical mechanical polishing defect test, the polishing pad material A' before process improvement, the polishing pad material A after process improvement, and the imported polishing pad material B are compared to analyze the influence of the polishing pad on the surface defects of silicon wafers when used in chemical mechanical polishing.

[0097] Fig.13 It is a defect map obtained by collecting and monitoring the silicon wafer after running the 60s test according to the plan in the test plan table. Among them, a) to c) are the defect maps corresponding to test condition 1 in Table 4; d) to f) are the defect maps corresponding to test condition 2 in Table 4; g) to i) are the defect maps corresponding to test condition 3 in Table 4. Silicon wafer surface defect distribution map, one point represents a defect, the more points, the more defects. Among them, a), d) and g) are defect maps after the polishing pad material A' test, b), e) and h) are defect maps after the polishing pad material A test, c), f) and i) are defect maps after the polishing pad material B test.

[0098] Depend on Fig.13 It can be seen that the surface defect removal rate of the polishing pad material A after the process improvement is greater than that of the polishing pad material A' before the process improvement, and the surface defects are smaller after using the polishing pad material A. However, there is still a certain gap compared with the surface defect removal rate of the silicon wafer after polishing with the imported polishing pad material B. This may be due to the relatively low porosity of the polishing pad material A and the relatively small microscopic pore structure. Therefore, the efficiency of absorbing and releasing the polishing liquid during the polishing process is low, resulting in relatively poor defect removal effect.

[0099] In summary, the preparation method of the polishing pad material provided by the present invention enables the polishing pad material to form a relatively stable and uniform microporous structure, so as to reduce the surface defects of the silicon wafer after polishing by the soft polishing pad material, and solves the technical problem that there are many surface defects of the silicon wafer after grinding by the existing polishing pad material. The polishing pad material prepared by the preparation method of the polishing pad material provided by the present invention can be successfully applied to chemical mechanical polishing processing.

[0100] The above description is only a preferred embodiment of the present invention, and the above specific embodiment is not intended to limit the present invention. Various deformations and modifications may occur within the scope of the technical concept of the present invention, and any modification, modification or equivalent replacement made by a person of ordinary skill in the art based on the above description shall fall within the scope of protection of the present invention.

Claims

1. A method for preparing a polishing pad material, characterized in that: The steps include: The impregnated cloth is immersed in water so that the water content of the impregnated cloth is between 25wt% and 28wt%, thereby obtaining a bass; The polyurethane slurry is evenly coated on the surface of the bass, and after solidification and forming, an intermediate is obtained; The intermediate is subjected to water washing, drying and surface treatment to obtain a polishing pad material; The concentration of the N,N-dimethylformamide solution used for solidification molding is 12wt% to 17wt%.

2. The method for preparing the polishing pad material according to claim 1, characterized in that: The coating thickness of the polyurethane slurry is 1.5 mm to 2.0 mm.

3. The method for preparing the polishing pad material according to claim 1, characterized in that: The solidification molding comprises the following steps: The bass coated with the polyurethane slurry is immersed in the N,N-dimethylformamide solution at a certain angle until it is completely immersed; Assume that the angle formed between the plane where the base coated with the polyurethane slurry is located and the liquid surface of the N,N-dimethylformamide solution is α, and the value of α is 25° to 35°.

4. The method for preparing the polishing pad material according to claim 1, characterized in that: The surface treatment includes grinding treatment and grooving treatment in sequence, wherein the grinding treatment is used to expose the pore structure of the polishing pad material, and the grooving treatment is used to form a surface groove structure on the surface of the polishing pad material.

5. The method for preparing the polishing pad material according to claim 1, characterized in that: The water washing process comprises: After intermittent water washing for 15 times, soak in water for 5 minutes to 15 minutes, and then intermittent water washing for another 15 times.

6. A polishing pad material, characterized in that: The polishing pad material is prepared by the preparation method of the polishing pad material according to any one of claims 1 to 5.

7. Use of the polishing pad material according to claim 7 in a chemical mechanical polishing process.

Citation Information

Cited By

  • Resolution trepanning polishing pad as well as preparation method and application thereof

    CN121733428A

  • A reverse etch open hole polishing pad, its preparation method and use

    CN121733428B